Cyp11b1 Is Induced in the Murine Gonad by Luteinizing Hormone/Human Chorionic Gonadotropin and Involved in the Production of 11-Ketotestosterone, a Major Fish Androgen: Conservation and Evolution of the Androgen Metabolic Pathway - Yazawa, Takashi; Uesaka, Miki; Inaoka, Yoshihiko; Mizutani, Tetsuya; Sekiguchi, Toshio; Kajitani, Takashi; Kitano, Takeshi; Umezawa, Akihiro; Miyamoto, Kaoru (Endocrinology (Philadelphia), 2008)
We have shown previously that Cyp11b1, an 11β-hydroxylase responsible for glucocorticoid biosynthesis in the adrenal gland, was induced by cAMP in androgen-producing Leydig-like cells derived from mesenchymal stem cells. We found that Cyp11b1 was induced in male Leydig cells, or female theca cells, when human chorionic gonadotropin was administered in immature mice. Expression of Cyp11b1 in rodent gonads caused the production of 11-ketotestosterone (11-KT), a major fish androgen, which induces male differentiation or spermatogenesis in fish. As in teleosts, plasma concentrations of 11-KT were elevated in human chorionic gonadotropin-treated mice. In contrast to teleosts, however, plasma concentrations of 11-KT were similar in both sexes, despite levels of testosterone, a precursor substrate, being about 20 times higher in male mice. Because expression of 11β-hydroxysteroid dehydrogenase type 2, was much higher in the mouse ovary than in the testis, conversion of testosterone into 11-KT may occur more efficiently in the ovary. In a luciferase reporter system that was responsive to and activated by androgens, 11-KT efficiently activated mammalian androgen receptor-mediated transactivation. Our results suggest that the androgen metabolic pathway is conserved between teleosts and mammals, despite sexual dominance and reproductive functions of 11-KT being altered during evolution.